2013
DOI: 10.1016/s2213-2600(13)70184-x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of four common pulmonary function tests to diagnosis of patients with respiratory symptoms: a prospective cohort study

Abstract: Belgian Society of Pneumology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
2
20
1
Order By: Relevance
“…Prior literature has examined the diagnostic yield of various tests among patients referred to specialty clinics for evaluation of shortness of breath. 6-11 These studies have shown spirometry to have the highest diagnostic yield, consistent with our results, as well as substantial benefit in chest imaging via X-ray or CT. For patients with normal spirometry and lung imaging, other tests such as diffusing capacity of the lung for carbon monoxide (DLCO), and exercise testing provided only incremental improvements in diagnostic accuracy. 6,7,11 No consistent approach to screening for cardiovascular causes has been presented in these prior studies, which were predominantly carried out in pulmonary clinics, and due to such problems of selection bias, the generalizability of their results remains unclear.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Prior literature has examined the diagnostic yield of various tests among patients referred to specialty clinics for evaluation of shortness of breath. 6-11 These studies have shown spirometry to have the highest diagnostic yield, consistent with our results, as well as substantial benefit in chest imaging via X-ray or CT. For patients with normal spirometry and lung imaging, other tests such as diffusing capacity of the lung for carbon monoxide (DLCO), and exercise testing provided only incremental improvements in diagnostic accuracy. 6,7,11 No consistent approach to screening for cardiovascular causes has been presented in these prior studies, which were predominantly carried out in pulmonary clinics, and due to such problems of selection bias, the generalizability of their results remains unclear.…”
Section: Discussionsupporting
confidence: 89%
“…Several algorithms have been proposed based upon the diagnostic yield of tests performed on dyspneic patients referred to specialty clinics, 5-11 yet no representative United States (US) population-based studies have been performed. Based on limited data, clinical guidelines recommend that a new complaint of dyspnea in adults warrants, in addition to a thorough history and physical, basic laboratory evaluation and preliminary diagnostic tests such as electrocardiogram (ECG), chest radiography, and possibly spirometry.…”
Section: Introductionmentioning
confidence: 99%
“…It does not mean that COPD with normal D LCO does not exist, yet the chance is low and therefore accepted as a mistake. Overall, the decision tree designed by the computer is approaching the accuracy of the expert panel, which reached 80% accuracy for healthy, asthma, ILD, NMD, and COPD based on the combination of 4 tests with clinical history [6] .…”
Section: Discussionmentioning
confidence: 95%
“…The study included the data of 968 subjects from the BPFS, a prospective cohort study that enrolled a clinical population-based sample of all successive undiagnosed patients admitted for the first time to one of the 33 participating Belgian hospitals due to respiratory symptoms [6] . The study was performed in the periods from June 6 to September 12, 2011, and from January 16 to June 12, 2012.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation